Characterization of fine-grained W–10 wt.% Cu composite fabricated by hot-shock consolidation. (September 2015) - Zhou, Qiang; Chen, Pengwan
Abstract: In this study the W–Cu composites have been fabricated by hot-shock consolidation and then their mechanical properties were estimated by nano-indentation experiments. The initial powders were preheated to 700–1000 °C in less than 3 min, then consolidated under shock pressure within range of 3–4 GPa instantaneously. A W–Cu composite with the highest relative density of 96.3% was obtained without any sintering activator. The grain size of consolidated sample is nearly the same as its initial size of 2 μm. The samples were characterized using light microscopy (LM) and scanning electron microscopy (SEM). It was found that the homogeneous distribution of copper is the key factor for the consolidation of W–Cu powder, which is dominated by preheating temperature. High temperature improves the distribution of copper and enhances the bonding of W–Cu, but also leads to agglomerating of Cu while exceeding a specific value. The main mechanisms of the densification of W particles are void collapse and plastic deformation, which are dominated by the shock pressure. Highlights: The W-Cu powders were preheated to 700-1000 °C in 3 mins, then consolidated under shock pressure within range of 3-4GPa. A crack-free composite with the highest relative density of 96.3% was obtained without any sintering activator. The grain sizes of all compacted samples are nearly the same as the initial powder. The homogeneous distribution of copper, which is dominated by preheating temperature, is the key factor.